Influence of first-order lateral reflections on the localization of virtual source reproduced by crosstalk cancellation system. (January 2023) - Tan, Wei; Yu, Guangzheng; Rao, Dan
Abstract: This study elucidates the influence of first-order lateral reflections on the localization of virtual sources reproduced by a crosstalk cancellation system. First, an experimental study was conducted to examine how the reflections with a delay within the scope of the summing localization and the precedence effect influence the localization of virtual sources with different frequency bands and target azimuths. The results show that the localization of virtual sources is influenced due to the reflections with a delay below the low limit of the precedence effect (1 ms universally), and the influence degree is related to the frequency band and target azimuth. When the delay is further increased, the effect of reflected sound is almost negligible. Particularly, for a virtual source in the region outside the loudspeaker on the contralateral side of the reflecting surface (at - 60 ° or - 90 ° ), the perceived azimuth under reflections with a small delay was more lateral than that without reflections. Then, simulations were conducted under the same conditions as the experiments. Based on the binaural signals modified by the inhibition function of the precedence effect, binaural cues, including interaural phase delay difference ( ITD p ) and interaural level difference, were calculated to explain the experimental results. Particularly, the average ITD p over frequency can qualitatively predict the localization results below 1.5 kHz from the subjective experiment in most cases.